Automation of Contagion Vigilance - Stodolsky, D. S. (Methods of Information in Medicine, 1997)
The very long latency between HIV infection and the appearance of AIDS imposes extensive information processing requirements on partner notification efforts. The apparently contradictory needs of maintaining the right to privacy of infected persons, while simultaneously providing information to persons at risk of infection, impose severe security requirements. These requirements can be satisfied by a Contagion Management System based upon networked personal computers of a kind now becoming available. Security of information is based upon cryptographic protocols that implement anonymous partner notification (contact tracing) and Privacy-Preserving Negotiation. The proposed scheme has the properties that contact tracing is automated, contacts remain anonymous, sensitive information is kept private, and risk-conscious users act as if sensitive information was public. Optimal health protection can thus be obtained while securing informational rights.
Keywords: Preventive Health Services; Patient Data Privacy; Real-time Systems; Distributed Databases; Epidemiology